Prototype of GIS based location information enquiry system - Ismail, Nur Zatul Iffah; Herman, Nanna Suryana; Sahib @ Sahibuddin, Shahrin; Devaraju, Anusuriya; Hassan, Aslinda; Muslim, Zulkifli (2006)
The convergence of the internet and wireless communication has led the popularity of using handheld devices. People have now started demanding services that can be delivered any time anywhere, called Location Based Services (LBS). This paper deal with development of location based services on handheld devices that apply to emergency services. Handheld devices suffer from serious constrains in three areas: memory size, processor speed and screen size. This application uses the client server concept within wireless internet environment. The positioning service such as GPS is used to know the position of the user. The objective of this research is to display special query on the required spatial information within handheld devices using different operating systems such as WinCE, Palm OS and Symbian. This implies the strong feature of the proposed system. Hence the system assists people e.g. at the time of emergency to find the shortest path to the nearest hospital. The application will be access through the wireless internet. Only the related location in the entire map will be displayed on the handheld devices to which gives the economical usage of bandwidth and resources for real time response. This technology uses mobile internet as web browser embedded in the handheld devices. In Malaysia, a Location Based Services is still new and can be expand in many ways, especially in emergency cases.